Fiscal Policy During Absorption Cycles - Salman, Ferhan (IMF Working Papers; Working Paper, 2011)
Domestic absorption cycles are relevant in assessment and design of fiscal policies. Our cross-country analysis covers 59 advanced and emerging countries for the 1990-2009 period. We show that ignoring domestic absorption cycles leads to biased fiscal stance indicators, for both advanced and emerging economies, by up to 1.5 percent of GDP. The estimates of fiscal policy reaction functions indicate that absorption booms are associated with pro-cyclical fiscal policy. We tackle the endogeneity problem in reactions functions through stripping the cyclical component of the fiscal aggregates. We also find that simple filtering methods in the computation of absorption gaps perform as better as indirect methods of estimating trade balance gaps and stripping of output gaps.